Bibliometric Analysis of the International Workshop on Advances in Cleaner Production in Brazil - Neto, Geraldo C. Oliveira; Shibao, Fábio Ytoshi (Journal of Environmental Accounting and Management, 2026)
The objective of this study was to evaluate the set of articles about cleaner production published in International Workshop on Advances in Cleaner Production (IWACP) Brazil in 2007. The methodology adopted was a bibliometric analysis using the UCINET-Draw software, which quantified and evaluated the scientific production inquestion in qualita-tive and quantitative terms. The primary constructs evaluated were as follows: (i) article thematics, methods used and segmentsresearched, (ii) relationships between thematics, segments and methods, (iii) the evolu-tion and the rate of rejection of articles from the IWACP (2007) for pub-lication in the Special Volume of the Journal of Cleaner Production (SJCP) (18) (2010) through an analysis of the citations in the ISI Web of Knowledge and a content analysis. The results demonstrate the general panorama of the IWACP (2007), allowing the proposition of future stud-ies in sustainability that focus on thematics, segments and methods. The results also show that the quality of the articles published in the SJCP (18) (2010) from the IWACP (2007) is similar to the other articles pub-lished in the Journal of Cleaner Production (JCP).